2007
DOI: 10.1093/jac/dkl522
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin-impregnated central venous catheters: a meta-analysis of randomized controlled trials

Abstract: Background: The use of antimicrobial-impregnated central venous catheters (CVCs) for the prevention of CVC microbial colonization and catheter-related bloodstream infection (CRBSI) remains controversial. Methods:We performed a meta-analysis of randomized controlled trials (RCTs) evaluating CRBSI and colonization of CVCs impregnated with rifampicin-based antimicrobial combinations. Our main analysis compared the occurrence of CRBSI with rifampicin/minocycline-impregnated CVCs with that of non-rifampicin-impregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 46 publications
0
48
0
5
Order By: Relevance
“…Two types of coating have been developed: minocycline-rifampin and chlorhexidine-silver sulfadiazine. Comparative studies concluded that the former is more efficient than the latter (200)(201)(202)(203)(204). However, the benefits of antibiotic coating for long-term intravenous catheters (LTIVC) have not yet been demonstrated.…”
Section: Currently Used Approaches Do Not Specifically Target Biofilmmentioning
confidence: 99%
“…Two types of coating have been developed: minocycline-rifampin and chlorhexidine-silver sulfadiazine. Comparative studies concluded that the former is more efficient than the latter (200)(201)(202)(203)(204). However, the benefits of antibiotic coating for long-term intravenous catheters (LTIVC) have not yet been demonstrated.…”
Section: Currently Used Approaches Do Not Specifically Target Biofilmmentioning
confidence: 99%
“…Coatings containing combinations of antibiotics and antiseptics like minocycline and rifampin or chlorohexidin and silver-sulfadiazine have been applied to the internal and external surface of catheters. In several studies these antimicrobial coated catheters were compared to non-coated catheters, and a reduction of catheter colonization and catheter related blood-stream infections were found [66][67][68]. The antimicrobial effect of antibiotics containing coatings was more pronounced than for the antiseptic coatings.…”
Section: Antibiotic Releasing Coatingsmentioning
confidence: 99%
“…The minocycline-rifampin combination in impregnated central venous catheters to prevent staphylococcal biofilm infections has proven to be very successful (79,204,205). This antibiotic combination has been extensively studied, with a recent meta-analysis of randomized controlled studies showing that these impregnated catheters resulted in fewer catheter-related bloodstream infections (CR-BSI) (odds ratio [OR] Ï­ 0.23) and less colonization (OR Ï­ 0.46) than for nonimpregnated catheters (79,205). Rifampin resistance also did not occur using these catheters, and this may be a costeffective approach to the prevention of infections for patients who require intravenous catheters for a prolonged time (79,205).…”
Section: Staphylococcimentioning
confidence: 99%